Associations of Ready-to-Eat Cereal Consumption and Income With Dietary Outcomes: Results From the National Health and Nutrition Examination Survey 2015–2018 - Smith, Jessica; Jain, Neha; Normington, James; Holschuh, Norton; Zhu, Yong (Frontiers in Nutrition, 2022)
Background: Ready-to-eat (RTE) cereal has been associated with higher diet quality but it is not known if this association differs by income. Objective: to investigate the association of RTE cereal with dietary outcomes in a US population stratified by income (measured using the poverty-to-income ratio (PIR)). Methods: Data from children 2 to 18 years (n= 5028) and adults 19 years and older (n=9813) with 24-hr dietary recalls from the cross-sectional, U.S. nationally-representative 2015-2016 and 2017-2018 National Health and Nutrition Examination Surveys (NHANES) were used in a multivariable linear model that included cereal eating status (based on day 1 24hr dietary recall), PIR category (Low-PIR <1.85; Mid-PIR 1.85 to 3.50; High-PIR >3.50) and their interaction. PIR is based on the ratio of the family household income to the poverty level set by the U.S. Department of Health and Human Services and higher PIR values indicate higher household income. Results: For children, there were positive associations between RTE cereal consumption and nutrient (e.g. iron, calcium, fiber, potassium and vitamin D p<0.001) and food group (e.g. whole grain and dairy p<0.001) intake and 2015-HEI (p<0.0001) but no association with PIR or RTE cereal-PIR interaction. For adults, PIR category was positively associated with the intake of nutrients (e.g. fiber, magnesium, potassium, and vitamin C p<0.001) as was RTE cereal consumption (e.g. fiber, calcium, vitamin D, potassium, vitamin B12, among others p<0.001). Both PIR and RTE cereal were positively associated with whole grain, dairy, and fruit (p<0.001) and 2015-HEI (p<0.0001) for adults. We also found a significant interaction between PIR and RTE cereal for adults for iron, phosphorus, B vitamins, and dairy (p<0.001). RTE cereal contributed to one quarter or more of daily intake, across all age and PIR groups, for several B vitamins, vitamin B6 and B12, iron, zinc, and whole grains. Added sugar intake was not associated with RTE cereal consumption in either children or adults. Conclusion: RTE cereal was associated with improved dietary outcomes, including increased intake of under-consumed nutrients, increased intake of recommended food groups, and higher diet quality, at all income levels. This work can help inform future dietary recommendations.